The sex chromosomes of Silene latifolia revisited and revised - Lengerova, Martina; Moore, Richard C; Grant, Sarah R; Vyskot, Boris (Genetics, 2003)
Classical studies have established that, during meiosis, the X and Y chromosomes of the model dioecious plant Silene latifolia pair over a region at the ends of their q arms. We used fluorescence in situ hybridization of two molecular markers to demonstrate that this widely accepted model is incorrect. From these data we conclude that the homologous arm of the X chromosome is the p arm and that of the Y chromosome is the q arm. The establishment of the proper orientation of the pseudoautosomal region is essential for mapping and evolutionary studies.
Keywords: Silene; Sex Determination Processes; In Situ Hybridization, Fluorescence; Sex Chromosomes; Chromosome Mapping; procesy určující pohlaví; molekulární evoluce; pohlavní chromozomy; Evolution, Molecular; mapování chromozomů; hybridizace in situ fluorescenční